2013
DOI: 10.1128/jvi.01264-13
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Gammaretrovirus Acquisition in Mus musculus Subspecies Carrying Functional Variants of the XPR1 Virus Receptor

Abstract: The xenotropic and polytropic mouse leukemia viruses (X-MLVs and P-MLVs, respectively) have different host ranges but use the same functionally polymorphic receptor, XPR1, for entry. Endogenous retroviruses (ERVs) of these 2 gammaretrovirus subtypes are largely segregated in different house mouse subspecies, but both MLV types are found in the classical strains of laboratory mice, which are genetic mosaics of 3 wild mouse subspecies. To describe the subspecies origins of laboratory mouse XP-MLV ERVs and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…Bxv1 is a nondefective X-ERV capable of producing infectious virus following chemical or immunological stimulation (54). These two ERVs are both found in the sequenced C57BL genome, and both are also found in the Japanese wild mouse M. m. molossinus (23,55). Bxv1 is the only active X-ERV in most inbred strains of mice (1) and is also thought to be active in Japanese mice (24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bxv1 is a nondefective X-ERV capable of producing infectious virus following chemical or immunological stimulation (54). These two ERVs are both found in the sequenced C57BL genome, and both are also found in the Japanese wild mouse M. m. molossinus (23,55). Bxv1 is the only active X-ERV in most inbred strains of mice (1) and is also thought to be active in Japanese mice (24).…”
Section: Resultsmentioning
confidence: 99%
“…Sources of inbred mouse strains, wild-caught and wild-derived mice, and mouse DNAs were described previously (23). Briefly, DNAs were isolated or obtained from mice maintained in our laboratory or from the randomly bred colonies of M. Potter (National Cancer Institute, Bethesda, MD), The Jackson Laboratory (Bar Harbor, ME), S. Rasheed (University of Southern California, Los Angeles, CA), R. Abe (Naval Medical Research Institute, Bethesda, MD), S. Chattopadhyay and H. Morse III (NIAID, Bethesda, MD), and RIKEN BioResource Center (Ibaraki, Japan), which participates in the National Bio-Resources (28).…”
Section: Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Terrestrial boreoeutherians, marsupials, and birds Marine and terrestrial boreoeutherians, marsupials, birds, reptiles, and amphibians (Anai et al, 2012;Bamunusinghe et al, 2013;Bolisetty et al, 2012;Elleder et al, 2012;Fiebig et al, 2006;Hanger et al, 2000;Jaratlerdsiri et al, 2009;Lamere et al, 2009;Martin et al, 1999;Patience et al, 2001;Tarlinton et al, 2013;Tristem et al, 1996;Wang et al, (Bertsch et al, 2009;Gayral et al, 2008;Iskra-Caruana et al, 2010;Kunii et al, 2004;Staginnus and Richert-Pöggeler, 2006) Furthermore, there is also a tendency for non-agriculturally and medically important viruses to be overlooked. As a result, it could thus be that the actual viral host range is much broader than surveillance of existing viruses alone could reveal.…”
Section: Boreoeutheriansmentioning
confidence: 99%
“…T6, T77, and T103, which promote Xpr1 protein expression, were homologous. Xpr1 induces apoptosis after binding to heterophil (Bamunusinghe et al, 2013) or polytropic retrovirus in humans. This result suggested that T6 induces senescence and apoptosis of black locust flower organs after retrovirus infection.…”
Section: Tdfs Related To Senescencementioning
confidence: 99%